Preparation of Nano-Crystalline ZnMn2O4 System by Sol-Gel Route - Deraz, N.M.; H. Abd-Elkader, Omar; Selim, M.M.; El-Shafey, O.; El-Asmy, A.A. (Asian Journal of Chemistry, 2014)
Morphological, structural and catalytic studies of nanostructures of ZnMn2O4 powders are presented. These powders were synthesized by sol-gel method with the calcination at 400-800 °C. The phase purity and crystal structure of investigated mixed oxides are carried out by powder X-ray diffraction. Scanning electron microscopy, transmission electron microscopy and energy dispersive X-ray allowed characterizing the morphology, microstructure and surface molar composition of these nano-materials. The catalytic activity was tested for the hydrogen peroxide decomposition in aqueous solution at 30-50 °C. The effects of calcination temperature on the structural, morphological and catalytic characteristics of the investigated solids were determined. The XRD results showed that the calcination temperature affect the solid state reaction between Zn and Mn oxides. It was found that the catalysts were active depending upon the smaller particle size of the as prepared solids.